Human Resource Management Challenges In Indonesian Business: An Empirical Investigation - Eva Latifah (Sean Institute, 2024)
This research aims to navigate Indonesia's dynamic business environment, seeking to identify key challenges in human resource management (HRM) through data-backed insights. A quantitative approach was used in the research with survey and interview methods to participants who are human resources (HR) working in various companies in Indonesia. The scope of the challenge focused on the role of HR management in planning, organizing, directing, and controlling. By applying quantitative analysis, this study seeks to provide recommendations based on empirical evidence to overcome HR management challenges. The results showed that the company faced significant challenges in HR management, especially related to inter-field coordination and miscoordination that hindered task execution. Regular evaluation through surveys, interviews, and document analysis is needed to identify program weaknesses and strengths, and to ensure that HR development programs are effective and adaptive to change. HR management must adopt a holistic and adaptive approach to deal with the increasingly complex diversity of employee characters. The implementation of continuous evaluation through surveys, interviews, and document analysis, as well as improving employee quality, satisfaction, and commitment, are key strategies in supporting the achievement of long-term strategic goals.